Early histological changes of ileal mucosa after augmentation cystoplasty - (:unkn) unknown (URBAN & FISCHER VERLAG, 2001)
Segments of bowel are used routinely for transplantation in various pathological conditions such as contracted bladders or poorly compliant neuropathic bladders. However, little is known how these intestinal segments adopt to a toxic environment caused by urine. Therefore, the present study was performed to determine early histological changes of ileal mucosa after augmentation cystoplasty. Seven patients with augmentation cystoplasty underwent random cold-cup biopsies of ileal segments after a mean period of 14.4 months after cystoplasty and morphological changes were evaluated using light microscopy and transmission and scanning electron microscopy. Most pronounced features were varying degrees of villous atrophy, increased numbers of Paneth and goblet cells. Severity of atrophic villous changes were not related to the length of the interval between surgery and endoscopic biopsy. These findings may be explained as adaptations of bowel tissue to counteract noxious effects of urine and to maintain its epithelial function in the bladder.
Keywords: augmentation cystoplasty; ileum; histology; ultrastructure; KOCK POUCH; URINARY-DIVERSION; ABNORMALITIES; RESERVOIR